2011
DOI: 10.2340/16501977-0816
|View full text |Cite
|
Sign up to set email alerts
|

Wii-based movement therapy to promote improved upper extremity function post-stroke: A pilot study

Abstract: An intensive 2-week protocol resulted in significant and clinically relevant improvements in functional motor ability post-stroke. These gains translated to improvement in activities of daily living.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(78 citation statements)
references
References 27 publications
4
63
0
11
Order By: Relevance
“…Research groups have only recently begun investigating virtual reality as a viable means of improving rehabilitation outcomes. Small-scale pilot studies have shown that individuals with stroke improved functional scores in the Wolf Motor Function Test and Fugl-Meyer Assessment after playing commercial virtual reality video games daily for 10 consecutive days [30]. These findings have been corroborated by numerous small studies.…”
Section: Introductionsupporting
confidence: 62%
“…Research groups have only recently begun investigating virtual reality as a viable means of improving rehabilitation outcomes. Small-scale pilot studies have shown that individuals with stroke improved functional scores in the Wolf Motor Function Test and Fugl-Meyer Assessment after playing commercial virtual reality video games daily for 10 consecutive days [30]. These findings have been corroborated by numerous small studies.…”
Section: Introductionsupporting
confidence: 62%
“…The use of VG in poststroke patients has demonstrated improvements in active and passive movements, as indicated by the Wolf Motor Function Test and Fugl-Meyer Assessment scores [5]. However, despite several case reports showing motor improvements in PD patients after exercising with VG, no clear evidence has been presented so far to show whether these exercises are beneficial to improve quality of life in PD patients.…”
Section: Introductionmentioning
confidence: 89%
“…McNulty et al [11] also conducted a study where stroke patients were asked to play Nintendo Wii Sports over 14 days with additional therapy. Wii Sports is a collection of mini-games, including: tennis, bowling, boxing, golf and baseball (that are all controlled using gestures with the Wii remote controller) that mimic the actual limb motions required for each sport [14].…”
Section: Related Workmentioning
confidence: 99%